Primary neuroendocrine carcinoma of breast with liver and bone metastasis detected with fluorine-18 fluorodeoxyglucose-positron emission tomography/computed tomography - Kamaleshwaran, Koramadai Karuppusamy (Medknow Publications & Media Pvt Ltd, 2014)
Cases of primary neuroendocrine carcinoma (NEC) of the breast have been reported, though rare. We report the case of a 45-year-old woman presented with jaundice and evaluated to have liver metastasis from neuroendocrine origin. She underwent whole body positron emission tomography/computed tomography, which showed left breast lesion and bone metastasis. Fine-needle aspiration (FNA) of breast revealed a NEC. A diagnosis of a primary NEC of the breast was rendered with hepatic and bone metastasis. She was treated with peptide receptor radionuclide therapy and is on follow-up.